1991
DOI: 10.1088/0029-5515/31/3/001
|View full text |Cite
|
Sign up to set email alerts
|

Helium transport in vented divertors and limiters

Abstract: The transport of neutral helium atoms near divertor or limiter target plates in fusion devices has been studied using Monte Carlo simulation techniques. The atomic processes of ionization of helium atoms by electron impact and elastic scattering with plasma ions are included as well as the thermal motion and the streaming of the ions along the magnetic field. The results obtained show significant effects of elastic collisions below about 10 eV, causing a substantial fraction of the helium atoms to be reflected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 16 publications
(27 reference statements)
0
11
0
Order By: Relevance
“…Earlier calculations suggested that elastic scattering of helium neutrals by hydrogenic ions could enhance helium atom transport towards the divertor [ 250,251]. Experimental measurements have shown that this process mainly heats the helium atoms in the divertor, thus increasing their mean free path [252].…”
Section: Helium Exhaust and Noble Gas Impurity Enrichmentmentioning
confidence: 99%
“…Earlier calculations suggested that elastic scattering of helium neutrals by hydrogenic ions could enhance helium atom transport towards the divertor [ 250,251]. Experimental measurements have shown that this process mainly heats the helium atoms in the divertor, thus increasing their mean free path [252].…”
Section: Helium Exhaust and Noble Gas Impurity Enrichmentmentioning
confidence: 99%
“…The beryllium concentration is estimated conservatively from JET beryllium limiter experiments [8,9]. Early calculations suggested that elastic scattering of helium neutrals by hydrogenic ions could enhance helium atom transport toward the divertor [10,11]. However, spectroscopic measurements have shown that this process mainly heats the helium atoms in the divertor [12], thus increasing their mean-free-path.…”
Section: Projection Of Iter Performancementioning
confidence: 99%
“…The differen-tial scattering is handled using cumulative probability tables for the cosine of the scattering angle [14,15].…”
Section: Description Of Simulationmentioning
confidence: 99%